Properties of direct aluminium bonded substrates for power semiconductor components - Lindemann, A.; Strauch, G. (2004 IEEE 35th Annual Power Electronics Specialists Conference (IEEE Cat. No.04CH37551), 2004)
Direct metal bonded ceramic substrates are used as carriers for silicon chips in a variety of power semiconductor devices such as most types of modules. They fulfill the task to electrically isolate the power electronic circuit from grounded heatsink, however providing a thermal path from the chips to the latter. While different types of ceramic substrates - such as aluminium oxide or aluminium nitride - are used, the metal layers bonded onto the ceramic plate almost exclusively consist of copper, leading to the designation direct copper bonded - DCB - substrate. In this paper a new combination of materials - Al/sub 2/O/sub 3/ ceramics in conjunction with bonded aluminium - is proposed: An overview about manufacturing technology of such direct aluminium bonded - DAB - substrates themselves and of components based on them is given. Further, electrical, thermal and mechanical properties of the substrates are characterised, being directly related to the subject of reliability. Characteristics expected based on physical considerations are compared to results gained in an extensive qualification program, comprising tests and measurements with bare substrates and complete power semiconductor components. As a reference, identically designed DCB substrates and components undergo the same program, permitting a direct comparison of results.